The Effect of Cebel-i Nusayri on Shaping of Latakia Sanjak Organization (Journal of Alevism-Bektashism Studies, 2020)
This paper’s subject is the administrative position that Latakia received after the 1864 Vilayet Law (Law of the Provinces). The focus is on the change from kaza status to sanjak, and the reasons that had effect on shaping of the administrative organization within this scope. This process, started with the establishment of the sanjak organisation in 1880, was aiming to ensure and maintain the Ottoman control and influence in the Latakia region, which can be called one of the “critical areas”. The opposing attitude of Nusayris, from the rugged region called Cebel-I Nusayri which extends on the eastern side of Latakia, against the policy of the Ottoman government in the scope of the Tanzimat reforms came to the fore. The reluctance and resistance to tax and military duty in the region led to the tension between this community, which constituted majority in the region, and the government. The efforts of the Ottoman government to prevent the opposition and to improve the conditions of sovereignty in this region influenced the formation of the sanjak organization in Latakia. Mithat Pasha, the vali/governor of the Syria at the time, as well as having an active role in the establishment of the sanjak, paid attention to detail of forming subunits such as kaza and nahiye. Accordingly, there were efforts to produce and apply administrative solutions that will be more effective on the control of settlements spread throughout the large mountain region in Latakia. As a result, the organization of the Margat and Sahyun kaza was necessary considering that a single district governorship could not be enough in the mountain region. According to the situation that emerged with the forming of a sanjak organization separate from the Tripoli sanjak, the Latakia administrative authority formed a local administrative unit consisted of four kaza, including Jableh/Cebele. A programme that would focus specifically on nahiye sand be supported by regulations to reinforce discipline conditions in the region, came subsequently. In the following years, besides the plan to establish a new district governorship in the mountain region, the actions set to increase and conduct military points with other administrative regulations, can be considered as related to the same aim.